Quantum Entropies and Decoherence for the Multiparticle Quantum Arnol’d Cat - Giorgio Mantica (Entropy, 2023)
I study the scaling behavior in the physical parameters of dynamical entropies, classical and quantum, in a specifically devised model of collision-induced decoherence in a chaotic system. The treatment is fully canonical and no approximations are involved or infinite limits taken. I present this model in a detailed way, in order to clarify my views in the debate about the nature, definition, and relevance of quantum chaos.